Is there an association between the ecological characteristics of anurans from the Brazilian Atlantic Forest and their extinction risk?. Issue 4 (3rd July 2020) - Anjos, Amanda G.; Costa, Renan N.; Brito, Daniel; Solé, Mirco
Abstract : Extinctions of anuran amphibians are more alarming compared to all other vertebrates. Several reports of declines come from Atlantic Forest, which currently holds only 1.62% of natural vegetation under full protection. However, despite this degradation, the Atlantic Forest still shelters a great diversity of anurans with a high diversity of specific ecological characteristics. Thus, our objective was to identify which ecological characteristics of anurans from the Atlantic Forest can be associated to this extinction risk, in order to understand how these characteristics can promote the species persistence against environmental disturbance. For each species, we gathered biological/ecological characteristics from literature, as well the extinction risk based on the National List of Endangered Species of Wildlife. In 2015, 547 anuran species had been assigned to the Atlantic Forest, of which 406 had their extinction risk defined. However, we considered only 295 species in our analyses due to the availability of biological/ecological information. We observed that the clutch size and the altitudinal distribution are related to the extinction risk of anurans. Threatened species had a small clutch size and were distributed in low or high areas, whereas non-threatened species had a larger clutch size and were distributed in intermediate altitude areas. Studies that investigate ecological characteristics that determine the extinction risk of species can be useful to assist conservation actions, concentrating efforts to species more sensitive to environmental alterations, besides highlighting the importance of natural history and the ecology of organisms in conservation decisions.